Preliminary Aquatic Ecology Assessment of a Coldwater Stream in the Black Hills Region of Wyoming - 巴利士 (2004)
黑丘陵代表北美一特殊生態區域，而砂溪被認為在區域內非常特別的水域生態系統。為了評估砂溪的保存價值，已清查與此溪流有關的文獻，而會且在1995及1999年在野外調查其水生植動物。關於黑丘陵區域砂溪獨特性質包括蜿蜓河道、常年流量源自冷水泉、豐富水生植被、及長鼻亞口魚(Catostomus catostomus)的孓遺族群。保存有害關的事項包括有集水區及溪岸過度放牧，造成棲息環境惡化，長期乾旱、河道變遷及地下水過度抽取，使得溪流量減少。 The Black Hills represent a unique ecoregion in North America, and Sand Creek has been considered a unique aquatic ecosystem in the region. To assess the preservation value of Sand Creek, relevant literature was reviewed and field surveys of its aquatic flora and fauna were performed in 1995 and 1999. Unique characteristics of Sand Creek in relation to the Black Hills region include a meandering channel of moderate gradient, large perennial flow originating from coldwater springs, abundant aquatic vegetation, and relict populations of longnose suckers (Catostomus catostomus). Preservation concerns include aquatic habitat degradation due to unregulated grazing in the area and long term decrease in streamflow due to drought, diversions, and groundwater depletion.